Reenvisioning the university education needs of wildlife conservation professionals in the United States. Issue 2 (1st February 2022) - Teel, Tara L.; Bruyere, Brett; Dayer, Ashley; Stoner, Kathryn E.; Bishop, Chad; Bruskotter, Jeremy; Freeman, Stephanie; Newmark, Jennifer; Jager, Corey; Manfredo, Michael J.
Abstract: The future viability of wildlife conservation in the United States hinges on the field's ability to adapt to changing social–ecological conditions including shifting societal values and mounting pressures to engage a greater diversity of voices in decision‐making. As wildlife agencies respond to calls to broaden their relevance amid such changes, there is a need to consider the role of university education programs in preparing future wildlife professionals to meet the challenges of this new era. We identify four core areas of competency (technical, leadership, administrative, and adaptive) for universities to consider integrating into new or existing programs to support the emergent needs of the wildlife profession. We focus on undergraduate degree programs as a critical foundation for wildlife‐related careers but also recommend consideration of these skill sets in other areas of professional development including graduate education. Our approach acknowledges the importance of building on traditional areas of expertise such as biology and expanding them to include more interdisciplinary training in areas such as systems approaches, the social sciences, and organizational change. We conclude with recommendations for implementation, highlighting several successful examples, for universities to contemplate as they explore programmatic changes to help build greater capacity for wildlife conservation in the 21st century. Abstract : We identify core areas of competency for universities to consider integrating into new or existing programs to support the emergent needs of the wildlife profession in the United States. By doing so, these programs will be better equipped to prepare the next generation of leaders, and ultimately the organizations that employ them, to address contemporary wildlife conservation challenges including societal change.